Analysis of the Application of Android-Based Financial Application Development to MSME Financial Statements in Pari Serdang Bedagai City Village - ,, Noviani; Chrisna, Haeriyati; Wahyuni, Sri; Sinaga, Miftahurrahmah (Journal of Community Research and Service, 2024)
In today's Digital Era, a financial report can be prepared using an android-based financial application by utilizing an android smartphone which will make it easier for MSME actors in Pari Serdang Bedagai City Village to see and enter transactions in the form of purchases-sales, debts-receivables, payment of operational expenses and others. This system makes it easier for MSME actors in Kota Pari Serdang Bedagai Village to find out business developments effectively and efficiently so that in the future it can be used as access to capital to formal financial institutions so that they can strengthen the economy in moving the wheels of the economy. The purpose of this study is to find out the process of implementing and developing a simple android-based financial application as a medium in compiling financial reports for MSMEs in Pari Serdang Bedagai City Village. This type of research is descriptive using a qualitative approach. The data analysis techniques used in this study include observation, interviews, and documentation. The results of this study were obtained that in the financial recording of MSMEs in the area in the village of Pari Serdang Bedagai City, they have not used android-based financial applications, they still use simple and manual recording. Their obstacle is the lack of knowledge about android-based financial applications in compiling financial reports due to the level of education and lack of socialization. From the results of research and discussion, it is known that the level of education in the IT field affects the application and development of android-based financial applications in compiling financial reports.